Exploring Connotative Meanings and Metaphors of Saudi Animal Proverbs: A Semantic and Pragmatic Analysis (Global Journal of Human-Social Science, 2022)
Proverbs tend to reflect a nation's social values, attitudes, and beliefs. The connotative meanings underlying animal proverbial sayings can either be affectionate or abusive based on the cultural aspects of the language under investigation. Although the semantic connotations of animal proverbs have been extensively studied, little scholarly attention has been paid to the proverbial expressions pertaining to animals in Saudi Arabia. The main aim of this study is to semantically and pragmatically investigate the connotations of animal proverbs in Hijazi Arabic in Saudi Arabia. The paper also seeks to deduce the representation of human-animal relation and explore the cultural values of the Hijazi society as depicted in the proverbs. The data is collected from different sources, mainly from a book of Hijazi proverbs by Atique (2018). About 11 animal proverbs were selected, classified and translated, both literally and figuratively, into English. The analysis of data is based on Lakoff and Johnson's (1980) Conceptual Metaphor Theory, the approaches involving Semantic Molecules proposed by Goddard (1998), and the theories of Cultural Linguistics introduced by Palmer (1996). The findings showed that human-animal interface is depicted through the conceptual mappings where animals function as a vehicle to express human characteristics, traits and behaviors. Moreover, the results revealed that all of the selected animal proverbs are evaluated negatively, except for one animal. Additionally, certain pragmatic functions were achieved using the proverbial expressions. There was also a variety of social and cultural underpinnings underlying these proverbs, which seem to have been transmitted from one generation to another.
Keywords: animals; conceptual metaphor theory; cultural linguistics; hijazi; pragmatic; proverbs; semantic molecules; social values